Bacterial cellulose biocomposites for guided tissue regeneration - Olyveira, Gabriel Molina de [UNESP]; Santos, Marcio Luiz dos [UNESP]; Manzine Costa, Ligia Maria; Daltro, Paula Braga [UNESP]; Basmaji, Pierre; Daltro, Gildysio de Cerqueira; Guastaldi, Antonio Carlos [UNESP] (Amer Scientific Publishers, 2014)
Bacterial cellulose (BC) has become established as a remarkably versatile biomaterial and can be used in a wide variety of scientific applications, especially for medical devices. In this work, the bacterial cellulose fermentation process is modified by the addition of chondroitin sulfate and hyaluronic acid (1% w/w) to the culture medium before the bacteria is inoculated. Besides, biomimetic precipitation of calcium phosphate of biological interest from simulated body fluid on bacterial cellulose was studied. Chondroitin sulfate and hyaluronic acid influences in bacterial cellulose were analyzed using transmission infrared spectroscopy (FTIR), XRD (X-ray diffraction) and scanning electron microscopy (SEM). FTIR analysis showed interaction between bacterial cellulose nanobiocomposites and calcium phosphate and XRD demonstrated amorphous calcium phosphate and calcium chloride on bacterial cellulose nanobiocomposites. SEM images confirmed incorporation of calcium phosphate in bacterial cellulose nanobiocomposites surface with different calcium phosphate particles morphology.
Keywords: Bacterial Cellulose; Nanoskin (R); Nanocomposites; Scaffolds; Dental Materials